PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS ADHD (Attention Deficit Hyperactivity Disorder) (GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIVITAS) DI SEKOLAH DASAR - Ina pujiyanti; Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Children with ADHD (Attention Deficit Hyperactivity Disorder) require educational services that are adaptive, structured, and responsive to their behavioral and learning needs. ADHD is a neurodevelopmental disorder characterized by difficulties in maintaining attention, hyperactive behavior, and impulsivity that affect academic achievement, social interaction, and emotional development. This article aims to describe the characteristics, learning barriers, educational strategies, and the role of teachers and parents in supporting children with ADHD in elementary schools. This study used a qualitative descriptive approach through a literature review method. Data sources were obtained from books, scientific journals, educational regulations, and references related to inclusive education and special needs education. Data were analyzed descriptively through stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that children with ADHD generally experience difficulties in concentrating, controlling impulses, sitting calmly for long periods, completing assignments independently, and maintaining social relationships with peers. In the learning process, children are easily distracted by surrounding stimuli and often display disruptive behaviors in the classroom. Therefore, schools need to create structured learning environments, provide adaptive teaching methods, use positive behavioral support, and offer emotional assistance. Teachers play a significant role in improving students’ concentration, self-control, social interaction, and academic achievement through engaging, student-centered, and varied instructional approaches. Collaboration between teachers, parents, and the school environment is also essential in supporting the optimal development of children with ADHD. Proper educational support can help children with ADHD develop academic competence, emotional regulation, social skills, independence, and self-confidence optimally within inclusive education settings. Keywords: ADHD, inclusive education, elementary school, children with special needs, hyperactivity